Descriptions of rituals - Hajdu, Péter (Primerjalna književnost, 2019)
Although the presentation of customs and rituals may refer to several actions, what makes them descriptions rather than narratives is a general approach that takes alternatives into consideration. If a series of possible events depends on many factors and a text presents all of these factors and alternative possibilities, the end result is a description. This is most obvious in simple texts (shown in the example of a product leaflet), while in sophisticated narratives such as a novel, descriptions of rituals tend to be from the characters' viewpoint instead of the narrator directly. The examples to be analysed have been taken from a medical leaflet providing patient information, an ethnographic text by Bronislaw Malinowski, and two twentieth-century popular novels (sci-fi and fantasy, respectively), The Dispossessed by Ursula K. Le Guin and Eric by Terry Pratchett, followed by a post-colonial novel, Adiga's The White Tiger.
Keywords: Adiga, Aravind; književnost in etnografija; Le Guin, Ursula; Malinowski, Bronisław; naratologija; običaji; obredi; opis; Pratchett, Terry